In vitro evaluation of clot quality and stability in a model of severe thrombocytopenia: effect of fibrinogen, factor XIII and thrombin-activatable fibrinolysis inhibitor - Shenkman, Boris (Edizioni SIMTI - SIMTI Servizi Srl, 2014)
BACKGROUND: The treatment options in severe thrombocytopenia (platelet count ≤20×10(9)/L) are limited. The aim of this study was to investigate ways of improving blood clotting and stability in reconstituted thrombocytopenia. MATERIALS AND METHODS: Thrombocytopenia (platelets [16±4]×10(9)/L) was created by differential centrifugation of normal blood followed by reconstitution of whole blood which was subjected to clotting in a rotation thromboelastometer by CaCl(2) and tissue factor, and to fibrinolysis by tissue plasminogen activator (tPA). In separate experiments, blood was diluted by 40% with TRIS/saline solution. Blood was treated with fibrinogen (fib), factor XIII (FXIII), and thrombin-activatable fibrinolysis inhibitor (TAFI). RESULTS: The maximum clot firmness of thrombocytopenic blood was approximately 2-fold less than that of intact blood. Supplementation of blood with fib and FXIII improved clot formation. In the presence of tPA, among fib, FXIII and TAFI, only fib stimulated clot propagation whereas each of these agents increased clot strength. There was a synergistic effect when fib was added together with FXIII or TAFI. Fibrinolysis was inhibited by TAFI and to a greater extent by TAFI + FXIII. Fourty percent dilution of blood reduced clot strength and increased susceptibility to tPA. Clot strength was increased by the treatments in the following order: fib/FXIII/TAFI > fib/TAFI > fib > TAFI > FXIII. In the presence of tPA, TAFI and FXIII lysed the clots significantly more slowly. This effect was stronger when blood was treated with the combination of fib/FXIII/TAFI. Doubling the fib concentration, alone or together with other agents, did not improve clot strength or stability. DISCUSSION: Augmentation of clot formation and anti-fibrinolysis by combining fib, FXIII and TAFI may be beneficial for the treatment of patients with severe thrombocytopenia especially when complicated by haemodilution following introduction of fluids to compensate for massive blood loss.